Polyurethane derived from Ricinus Communis as graft for bone defect treatments - Sousa,Tatiana Peixoto Telles de (2018)
Abstract This work evaluated polyurethane (Polyquil®) as a graft for treatment of bone defects. Bone defects of 1.5 × 0.5 cm were made in the calvaria of 16 rabbits. Eight animals had their defects treated with Polyurethane (Treated) and 8 of them had their defects filled with blood clot (Control). In the second experiment, segmental defects of 0.5 cm were performed at the zygomatic arch of 16 rabbits. Eight animals were treated by guided bone regeneration, using a latex membrane, associated to grafting of polyurethane while the others were not treated (Control). The bone tissue morphometry in the craniotomy experiment resulted in a higher bone volume in the Treated group at 60 days (p <0.05, t student test). Microscopic and radiographic images demonstrate the formation of a bone bridge in the segmental defect, 60 and 120 days after surgery in the Treated group, different from the Control group with incomplete healing.